Implementation of the Principle of Sic Utere Tuo Ut Alienum Non Laedas Towards Cases of Transboundary Haze Pollution in the Southeast Asian Region - Ilham Aldi Nugroho; Ria Tri Vinata (Asian Journal of Environmental Research, 2026)
Forest and land fires in Indonesia have repeatedly caused transboundary haze pollution that affects several Southeast Asian countries, particularly Malaysia, Singapore, and Brunei Darussalam. This situation raises an important question of state responsibility under international environmental law, especially through the principle of sic utere tuo ut alienum non laedas, which requires states to use their territory and natural resources in a manner that does not cause harm to other states. This principle is reflected in the 1972 Stockholm Declaration, the 1992 Rio Declaration, and the ASEAN Agreement on Transboundary Haze Pollution, which provides a regional framework for preventing and controlling transboundary haze. This study uses normative legal research with statutory and conceptual approaches to examine how the principle operates in the context of transboundary haze pollution in Southeast Asia. The analysis shows that the implementation of this principle requires states to exercise due diligence through prevention, monitoring, law enforcement, and regional cooperation. However, its effectiveness remains constrained by weak environmental enforcement, limited compliance mechanisms under ASEAN, and the persistence of the non-interference principle in regional governance. Strengthening the implementation of sic utere tuo ut alienum non laedas is therefore essential not only for state accountability, but also for protecting regional ecosystems, reducing greenhouse gas emissions from forest and land fires, supporting climate change mitigation, and advancing environmental justice and regional public health in Southeast Asia.